Methyl isocyanide as a convertible functional group for the synthesis of spirocyclic oxindole γ-lactams via post-Ugi-4CR/transamidation/cyclization in a one-pot, three-step sequence - Maddirala, Amarendar Reddy; Andreana, Peter R. (Beilstein Journal of Organic Chemistry, 2018)
The synthesis of spiro[indoline-3,2'-pyrrole]-2,5'(1'H)-diones and spiro[indoline-3,2'-pyrrolidine]-2,5'-diones, via a post-Ugi-domino transamidation/cyclization sequential process, has been achieved in three sequential steps utilizing a one-pot reaction protocol. The variation in carboxylic acid substrates allows for the generation of new chiral racemic quaternary carbon centers under basic conditions providing molecular diversity and a small library of spirocyclic oxindoles.
Keywords: convertible isocyanides; lactams; molecular diversity; oxindoles; transamidation